Diversidade ecológica e genética em populações de Hypsiboas puchellus (Hylidae) de dois biomas da América do Sul - Ugioni, Luiz Fernando Rocha [UNIFESP] (2013)
Biological diversification generates patterns of genetic diversity, be it driven by neutral biogeographic (variance and dispersal) or populational (demographic fluctuation) or even adaptive processes mediated by natural selection (e.g., selection along ecological gradients). We undertook a study on the ecological and phylogeographical diversity of an amphibian widespread in the the subtropics of South America that occurs in three distinct biomes. Firstly, we used multivariate analyses to test if bioclimatic niche components of H.pulchellus indicated niche divergence or conservatism along a spatially autocorrelated ecological gradient. Secondly, we used present day species distribution models to make projections of the impact of Pleistocene climatic fluctuations (specifically, the last glacial maximum, 21K years ago) on the geographic range of H.pulchellus. Thirdly, we performed phylogenetic analyses using maximum parsimony and maximum likelihood methods to check if multiple independent lineages existed within the species H. pulchellus, and if those would be geographically associated with distinct biomes across the species range. Fourthly, we looked for biome associated geographic population structure within H.pulchellus, both with a bayesian analysis and a traditional analysis of molecular variance, respectively, without and with a priori defined groups. Fifthly, we used tests based on summary statistics to examine the hypothesis that populations of H.pulchellus of distinct biomes had distinct demographic histories. Multivariate analyses showed that the species bioclimatic niche is distinct in each biome which may suggest some degree of ecological divergence between populations in each region. The species paleodistribution projection (LGM) suggests species range stability, i.e., that Pleistocene climatic fluctuations did not drive diversification within H.pulchellus. Phylogenetic analyses of mitochondrial and nuclear DNA gene fragments did not uncover evolutionarily independ at lineages within H. pulchellus. A contrasting patterns was however apparent for mtDNA where divergente haplotypes were more commonly observed in regions of high altitude in the Atlantic forest, at Rio Grande do Sul, while most sites in lowland regions throughout the species range showed an excess of less divergent and rarer haplotypes. Analyses of molecular variance did not uncover phylogeographic structure associated with the Atlantic forest and the Pampa biomes, but bayesian inference of population structure, for both mtDNA and nDNA, consistently uncovered a geographic group of localities of the highlands of the Atlantic forest that tends to be genetically distinct from neighboring regions. Finally, one test of demographic fluctuation vs. stability (Fu’s Fs) showed that populations in the Pampa region may have experienced demographic expansion while those in the Atlantic forest may have been relatively stable.